Towards the strategic adoption of Lean in aviation Maintenance Repair and Overhaul (MRO) industry: an empirical study into the industry’s Lean status - Ayeni, Peter; Ball, Peter D.; Baines, Tim S. (Emerald, 2016)
Despite many Maintenance Repair and Overhaul (MRO) organisations alluding their positive business performances to the adoption Lean initiatives, there is a paucity of direct literature that validates this assertion. Thus, the purpose of this paper is to study empirically via the use of an industry-wide survey to establish and extent of Lean adoption and to verify its suitability in mitigating prevalent MRO challenges. Design/methodology/approach The empirical study contained in this paper is facilitated by an industry-wide survey to collect data from several firms across the MRO spectrum. The analysed responses from industry leaders, professionals and executives synthesised with existing literature was used in ascertaining the extent of Lean adoption within the operational framework of the industry. Findings The empirical study helped in validating the suitability of Lean in MRO context. However, it was also observed that the focus of its application was skewed towards its production-orientated functions more than its service-orientated functions. Nonetheless, this paper presents results of the positive influence of Lean in MRO context. Research limitations/implications This empirical study presented in this paper was carried out within a framework of key characteristics of operation. Although this approach is sufficient in assessing the industry’s Lean status, further assessment can also be achieved within the context of relevant performance metrics which was not included in this paper. Practical implications By exploring the industry’s Lean status within the context of operational characteristics of operation, this study provides MRO practitioners with more awareness into some of the critical factors required for successful holistic Lean realisation. Social implications The state-of-the-art of Lean within the aviation MRO context established through this research also contributes to the wider product-centric service environment by providing a platform that facilitates strategy development which ensures Lean success within this environment. Originality/value Apart from validating the suitability of Lean in MRO contexts, by establishing the extent of Lean adoption within the context of the operational framework, this paper provides a clearer insight as to how successful Lean implementation can be achieved via a holistic implementation strategy balanced between the product-centric and service-centric aspects of the industry.
Keywords: decision making; Continuous improvement; Lean; customer relations; best practice; value